2021
DOI: 10.3390/ani11061832
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Gland Ultrasonographic Measurements and Plasma Hormone Concentrations in Clinically Healthy Newborn Thoroughbred and Standardbred Foals

Abstract: Adrenal hormones, ACTH plasma concentrations and the ultrasonographic evaluation of the adrenal glands are considered complementary in clinical evaluations of the hypothalamic–pituitary–adrenal (HPA) axis function in several species. In dogs, age, size and weight have a significant effect on the ultrasonographic size of the adrenal glands. In neonatal foals, ultrasonographic evaluation and measurements of the adrenal glands have been demonstrated to be reliable; however, the effect of individual variables on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Although there may be justification for including these endocrine measurements, they are not reliable parameters as unique indicators of pain in horses [ 2 ]. It is argued that there may be a variable in relation to the breed, as was observed in a comparative study between the response of the adrenal glands between ten purebred and standard breed foals where it was observed that the levels of cortisol, progesterone, adrenocorticotropin, and aldosterone were higher in purebred animals compared to standard breed animals, as well as a significant difference in the size of the adrenal medulla between these animals, which suggests a characteristic to consider for the evaluation of this analyte [ 113 ].…”
Section: Endocrine Alterations Associated With Pain and Anxiety Improvementioning
confidence: 99%
“…Although there may be justification for including these endocrine measurements, they are not reliable parameters as unique indicators of pain in horses [ 2 ]. It is argued that there may be a variable in relation to the breed, as was observed in a comparative study between the response of the adrenal glands between ten purebred and standard breed foals where it was observed that the levels of cortisol, progesterone, adrenocorticotropin, and aldosterone were higher in purebred animals compared to standard breed animals, as well as a significant difference in the size of the adrenal medulla between these animals, which suggests a characteristic to consider for the evaluation of this analyte [ 113 ].…”
Section: Endocrine Alterations Associated With Pain and Anxiety Improvementioning
confidence: 99%